Clinical physiology and sleep: highlights from the European Respiratory Society Congress 2018 presented by early career members - Almendros, Isaac; Aliverti, Andrea (Journal of Thoracic Disease; Vol 10, Supplement 25 (September 2018): Journal of Thoracic Disease [Dedicated to the 28th International Congress of the European Respiratory Society (ERS 2018)], 2018)
The 2018 Annual Congress of the European Respiratory Society (ERS) held in Paris has featured the novel insights on sleep and clinical physiology. The ERS Congress provides an excellent opportunity to young pneumologists and researchers to present their work to the recognized experts in their fields. This year, we highlight some of the best rank studies carried out by early career members from assembly 4.